Heavy Metal Content of Roadside Soils along Ring Road in Riyadh (Saudi Arabia) - Al-Shayeb, S.M.; Seaward, M.R.D. (Asian Journal of Chemistry, 2010)
The metal content (Pb, Zn, Cu, Cr and Ni) of roadside surface and subsurface soils was determined along the Ring Road in Riyadh city. Their levels were investigated in relation to traffic loads and distance from the road edge. Results showed that enhanced levels of Pb, Zn and Cu correlated well with traffic density. The concentration of Pb and Zn decreased exponentially with distance from the road edge and dropped to a background level at about 40 and 30 m respectively. Cr correlated well with Pb indicating the same source. No evidence of Ni contamination of roadside soils was obtained. Concentrations of Pb, Zn and Cu showed enrichment in the upper surface soils, which is attributed to the low rainfall in the study area. An important source of lead is the combustion of leaded gasoline used for transportation in Saudi Arabia.